The Impenetrable Animal Heart: Descartes and Condillac on Animals [el Impenetrable Corazón Animal: Descartes y Condillac Ante Los Animales] - Neira-Barrera, H (2013)
During French modernity, comparison between animals and humans is a key to understand what "human" is, as shown by Descartes s and Condillac s works. An analysis of these works allows us to see how, during modernity, two questions about animals arise. (i) How might one establish a foundation for a resemblance between humans and animals or, on the contrary, consider it illegitimate? (ii) How could one speak philosophically about animals if part of their essence seems to consist of being impenetrable for human knowledge? Reflecting on the position of Descartes and Condillac on animals makes it possible to clarify some of the challenges that contemporary zoophilosophy must solve. © 2013 by Unisinos.